Penerapan Teori Organisasi dalam Penguatan Kapasitas Kelembagaan UMKM di Desa Sukamaju - Sandra Nufadila Setia Ningsih; Suwandi (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) institutions have a strategic role in local economic growth. However, many MSME groups in rural areas do not yet have adequate organizational structures, which results in weak coordination and business productivity. This community service aims to apply concepts in organizational theory to improve the effectiveness of MSME institutions in Sukamaju Village. The organizational theories used include contingency structure theory and open systems, which are applied in the form of training, group discussions, and direct assistance. The results show an increase in the ability of MSME members to understand the importance of role division, communication flow, and adaptability to market changes. This service recommends further implementation in the form of in-depth training per field of organizational function